Perception of diabetes control among patients with poor glycated hemoglobin - Shahar, Mohammad Arif; Tahir, Mohd Faiz; Omar, Ahmad Marzuki (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia., 2017)
Introduction: Despite advances in the management of diabetes, the rate of control of diabetes in the population remains modest. Perception of diabetes control is a key to patient empowerment. The aim of this study was to describe the perception of diabetes control among patient with poorly controlled diabetes. Materials and method: A cross sectional study was done involving 276 patients with type 2 diabetes mellitus in the out-patient settings. After obtaining an informed consent, the socio-demography and medical history of each patient was recorded. Their most recent available blood investigations were documented. Patients were then asked on their perception of diabetes control whether it was excellent, moderate or poor. Analyses were descriptive and exploratory. Results: The median age of subjects was 56.0 (48.0,62.0) years old, with a median duration of diabetes of 8 (4,13) years. The median HbA1C was 9.5 (8.3,11.4)% with a fasting blood sugar of 9.7 (7.1,13.8) mmol/L. Despite having poor HbA1C, 28.4% of patients perceived that their diabetes control was excellent; 58.9% perceived moderate and only 12.7% accurately perceived poor control. The reverse relationship between perception of disease and education may indicate that other factors such as effective communication might need to be considered. The absence of association between perception and duration of diabetes may suggest that information given to patient over the years had poor impact on their understanding of disease control. Conclusion: This study demonstrated that there was presence of discordance between perception of diabetes control and HbA1C. Identifying the discordance between perception of diabetes control and HbA1C should be the first step in delivering a personalized diabetes education for patient.